Qualitative and Quantitative Investigation of Iraqi Grapefruit ( Citrus padisi) Flavonoids From Peel and Seeds and Comparing Their Aqueous Extracts for Antimicrobial Activity - Al-Ogaili, Niran A.; Yasin, Zainab (Iraqi Journal of Science, 2022)
Iraqi grapefruit ( Citrus paradisi, family Rutaceae) flavonoids were investigated qualitatively and quantitatively. The total isolated flavonoids from seeds and peel were 3.6 mg and 12.53 mg respectively in each gram of powder. The antimicrobial activity of aqueous extracts and total isolated flavonoids from seeds and peel were assessed against strains of Gram positive bacteria( Staphylococcus aureus, Staphylococcus epidermidis), Gram negative bacteria( Escherichia coli, Pseudomonas aeruginosa) and yeast( Candida albicans). The aqueous extracts lacked antimicrobial activity against all bacteria and yeast, while the total flavonoids showed a moderate inhibitory effect against test bacteria and yeast. This difference in inhibitory activity between aqueous extract and total flavonoids may be due to structurally-related aspects.